2022
DOI: 10.29333/ejmste/12514
|View full text |Cite
|
Sign up to set email alerts
|

Educational reflections on the coronavirus pandemic in three different countries

Abstract: The coronavirus that emerged in Wuhan, China, in 2020 has affected the world and become a global pandemic. All systems in the world are in place to prevent the spread of the pandemic. The education system is one of those systems. Schools are closed to prevent the spread of the virus and to allow a mandatory transition to emergency distance education. The development, change, and difficulties that occurred in the education system in the Northern Cyprus (NC), the Republic of Turkey(TR), and the Russian Federatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Interviewees also predicted that emerging technologies like virtual simulations and AI tutors would enable more personalized, immersive learning. Similar conclusions have been drawn in research envisioning how tools like augmented reality and intelligent adaptive learning systems could transform medical education (Aungst & Patel, 2020;Sorakin et al, 2022;Uzunboylu et al, 2022;Zhdanov et al, 2023). However, interviewees cautioned that over-dependence on technology could potentially impede development of core clinical skills and humanistic values.…”
Section: Discussionmentioning
confidence: 61%
“…Interviewees also predicted that emerging technologies like virtual simulations and AI tutors would enable more personalized, immersive learning. Similar conclusions have been drawn in research envisioning how tools like augmented reality and intelligent adaptive learning systems could transform medical education (Aungst & Patel, 2020;Sorakin et al, 2022;Uzunboylu et al, 2022;Zhdanov et al, 2023). However, interviewees cautioned that over-dependence on technology could potentially impede development of core clinical skills and humanistic values.…”
Section: Discussionmentioning
confidence: 61%
“…Our scoping review and our student surveys confirmed that students were upset at being deprived of physical proximity to their friends. 13 In-person school attendance and school connectedness serve as protective factors for children's mental health. 14 Conversely, restricted social connections can increase the risk of anxiety disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have been carried out to look into how digital learning environments affect student outcomes (Masalimova et al, 2022;Qarkaxhja et al, 2021;Sorakin et al, 2022). According to Papamitsiou et al's (2016) meta-analysis, when compared to traditional face-to-face classes, online education was equally effective in terms of student learning outcomes in 2016 with no discernible differences in performance.…”
Section: / 10mentioning
confidence: 99%